Solid organ transplantation and pregnancy - M.A. Lysenko; P.V. Kozlov; V.M. Grabovskiy; I.Yu. Kokaya; I.P. Osokin (LCC «Medicine-Inform», 2021)
M.A. Lysenko1, P.V. Kozlov2, V.M. Grabovskiy1, I.Yu. Kokaya1, I.P. Osokin1 1City Clinical Hospital No. 52, Moscow, Russian Federation 2Pirogov Russian National Research Medical University, Moscow, Russian Federation This paper highlights the management of pregnancy, delivery, and the postpartum period after solid organ transplantation. First, statistical data on the prevalence and pattern of organ transplantation are addressed. The most relevant issues of pregnancy management in organ transplant recipients include identifying optimal criteria of transplant function monitoring, assessment of pregnancy and medication effects on the fetus, and pregnancy complication development. Next, the authors review major pharmacological classes of immunosuppressive therapy, pregnancy risks, complications, and outcomes associated with these medications, relevant pregnancy planning and management issues, and delivery in liver and kidney transplant recipients. Finally, the effect of breastfeeding (in the context of regular immunosuppressive therapy) on the postnatal period is discussed. Current data demonstrate that favorable pregnancy outcome after organ transplantation is most likely at least one year after transplantation in case of stable organ functioning, careful monitoring of recipient and transplant, adequate immunosuppressive therapy, diagnostic monitoring of fetus throughout pregnancy, and timely delivery. Keywords: pregnancy, transplantation, liver, kidney, immunosuppressive therapy, complications, breastfeeding. For citation: Lysenko M.A., Kozlov P.V., Grabovskiy V.M. et al. Solid organ transplantation and pregnancy. Russian Journal of Woman and Child Health. 2021;4(4):333-338 (in Russ.). DOI: 10.32364/2618-8430-2021-4-4-333-338.